Facebook Usage and Secondary School Students’ English Language Performance in Akungba-Akoko, Ondo State, Nigeria - Ogunyemi, Kehinde (Universitas Kapuas, 2025)
The rapid proliferation of social media has significantly impacted communication and learning, with Facebook being one of the most widely used platforms among students. While Facebook offers educational benefits, concerns have arisen regarding its potential impact on students' academic performance. This study examines the relationship between Facebook usage and secondary school students' performance in English Language with a focus on Akungba-Akoko, Ondo State, Nigeria. Using a survey research design, data were collected from 105 senior secondary school students through a structured questionnaire. The study assessed the frequency and duration of Facebook usage, as well as students' academic performance in English Language. Results revealed that a majority of students (63.81%) accessed Facebook daily, with 46.67% spending between 30 minutes to 1 hour per session. The analysis of academic records indicated that over 80% of the students scored below the average grade in English Language. However, the regression analysis demonstrated no significant relationship between Facebook usage and students' academic performance (R² = 0.001696, p > 0.05), suggesting that while students frequently engage with Facebook, its impact on academic outcomes is negligible. The study concludes that other factors, such as study habits and access to learning resources, may play a more substantial role in influencing English Language proficiency. Based on these findings, it is recommended that educators and policymakers focus on improving teaching methodologies and providing adequate learning materials rather than solely discouraging Facebook usage. Additionally, students should be encouraged to balance their social media activities with academic responsibilities to maximize learning outcomes.